A selenium-induced defective copper-based sulfur / selenide material and its preparation method and application

Through the preparation of selenium-induced defective copper-based sulfur/selenide materials, Cu1.96S and CuSe heterojunction structures, the problem of volume expansion and low conductivity of the negative electrode material of sodium ion battery during charging and discharging is solved, and high storage is achieved Sodium capacity, long cycle life and high rate performance effects.

CN118877924BActive Publication Date: 2025-02-25LUOYANG INST OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411364944.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-25
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The negative electrode material of sodium ion battery is prone to volume expansion and structural collapse during charging and discharging, resulting in rapid capacity decay and shortened battery life, and the material's conductivity is low and the ion transport dynamics process is slow.

Method used

Cu1.96S and CuSe heterojunction materials with copper-rich vacancies were prepared by co-precipitation and pyrolytic selenization strategies to improve the conductivity and electrochemical properties of the materials.

Benefits of technology

It significantly improves the conductivity and electrochemical properties of the material, enhances the sodium storage capacity and rate performance, extends the cycle life of the battery, and reduces the cost of raw materials and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118877924B_ABST
    Figure CN118877924B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of sodium ion battery electrode materials, specifically a selenium-induced defect copper-based sulfur / selenide material and its preparation method and application, and a novel copper-based metal organic framework compound Cys-Cu precursor is preferentially prepared by a coprecipitation strategy; the precursor and a selenium source are then pyrolyzed and selenized under an inert atmosphere, and then naturally cooled to room temperature to obtain a product. The preparation method makes full use of the advantages of heteroatoms such as S / N in the ligand in the precursor, and a copper-based sulfur-selenide composite material with rich vacancies is obtained only by the preparation and selenization of the precursor, and the manufacturing process is simple and efficient, the cycle is short, and the stability is good. The composite material obtained by the method contains rich cation vacancies and a heterogeneous interface spontaneously constructed by copper-based sulfide and selenide, which can not only improve the material conductivity, promote effective electron / ion transport, but also create more sodium storage active sites, and further improve the material sodium storage capacity and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery electrode materials, and in particular to a selenium-induced defect copper-based sulfur / selenide material, a preparation method thereof, and an application thereof. Background Art

[0002] Sodium-ion batteries (SIBs) have been the subject of intense research as a promising alternative to lithium-ion batteries due to their low cost, abundant sodium resources, stable low-temperature performance, and high safety. However, the large ionic radius of sodium ions results in slow charge and discharge kinetics, limiting their widespread application. As a crucial component of batteries, the rational design and performance improvement of anode materials can significantly enhance the capacity, rate capability, and cycle performance of sodium-ion batteries.

[0003] Copper-based chalcogenides based on conversion reactions can provide high sodium storage capacity through a multi-electron transfer mechanism. However, the formation of Na2S and Na2Se during charge and discharge inevitably leads to volume expansion and structural collapse of the negative electrode material, resulting in rapid capacity decay and shortened battery life. In addition, the inherent semiconductor properties of copper-based chalcogenides lead to large charge transfer impedance and slow ion transport kinetics. To address the problems of volume expansion and low conductivity, reasonable structural design and fine-tuning of component optimization are key to overcoming volume expansion, improving material conductivity, and enhancing sodium storage performance. Structural engineering, vacancy engineering, and interface engineering are considered to be effective strategies to address the above problems. Reasonable structural design, such as hierarchical structure, hollow structure, core-shell structure, etc., can effectively relieve the stress during the sodium embedding process of the material, increase the specific surface area of ​​the material, increase its contact area with the electrolyte, provide more active sites, and shorten the ion diffusion distance; vacancy engineering, such as cation vacancies and anion vacancies, can regulate the electronic structure of the host material, enhance the conductivity of the material, improve the rate performance, and provide more active sites for sodium storage; interface engineering, such as heterojunction, can introduce new phases into a single phase and form heterojunctions, which can improve electronic conductivity, reduce the sodium ion diffusion energy barrier, and alleviate polarization. The copper-based sulfide or selenide negative electrode materials currently prepared using the above strategies are complex processes, have high raw material costs, and have certain toxicity. Therefore, the preparation of copper-based negative electrode materials with high sodium storage activity can be achieved through simple processes, which is of great significance. Summary of the Invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a selenium-induced defect copper-based sulfur / selenide material and its preparation method and application, the copper-based sulfur / selenide composite material contains copper-rich vacancies 1.96 S and CuSe active sites can improve the conductivity and electrochemical properties of the material.

[0005] In order to achieve the above object, the present invention discloses a method for preparing a selenium-induced defect copper-based sulfur / selenide material, comprising the following steps:

[0006] (1) Dissolve copper acetate (Cu(CH3COO)2•H2O) in water to prepare solution A, dissolve cysteine ​​in water, and after it is completely dissolved, add NaOH solution to adjust the pH value of the cysteine ​​solution to alkaline to obtain solution B. Then, add solution A to solution B and stir the mixture in a constant temperature water bath to react. After the reaction is completed, centrifuge the obtained mixed solution, discard the upper liquid, and obtain the lower precipitate. The precipitate is washed by centrifugation several times with water and then vacuum dried to obtain a Cys-Cu precursor.

[0007] (2) Place the Cys-Cu precursor in porcelain boat A and the selenium powder in porcelain boat B. Then place porcelain boat B in the upstream of a dual-temperature zone tubular furnace and porcelain boat A in the downstream of the dual-temperature zone tubular furnace. Heat the mixture to a certain temperature under an inert atmosphere and keep the temperature constant for a period of time. After the constant temperature is reached, cool the mixture naturally to room temperature to obtain selenium-induced defect copper-based sulfur / selenide materials.

[0008] Furthermore, in step (1), the molar concentration of copper acetate in solution A is 0.02-0.06 mol / L, and the molar concentration of cysteine ​​in solution B is 0.01-0.02 mol / L; the speed of centrifugation is 5000-10000 rpm, and the time of each centrifugation is 3-8 minutes; and the drying temperature is 50-80°C.

[0009] Furthermore, in step (1), the water used is deionized water; the concentration of the NaOH solution is 1-4 mol / L, the volume of the added NaOH solution is 5-15 mL, and the pH value of solution B is 8-12; the temperature of the constant temperature water bath is 20-40°C, and the stirring reaction time is 0.2-30 hours;

[0010] Furthermore, in step (2), the mass ratio of the Cys-Cu precursor to the selenium powder is 1:1 to 1:6.

[0011] Furthermore, in step (2), the heating rate is 2-5°C / min, the temperature is raised to 300-600°C, the constant temperature time is 1-5 hours, and the inert atmosphere is N2 atmosphere.

[0012] The present invention also discloses a selenium-induced defect copper-based sulfur / selenide material obtained according to the preparation method and the application of the selenium-induced defect copper-based sulfur / selenide material as a negative electrode material for a sodium ion battery.

[0013] Furthermore, the selenium-induced defective copper-based sulfur / selenide material contains Cu 1.96 S and CuSe, and Cu1.96 A homologous heterojunction is formed between S and CuSe.

[0014] The present invention forms a novel metal organic framework compound by simple coprecipitation with copper acetate as the metal source and cysteine ​​as the organic ligand. Then, the novel metal organic framework compound is used as a precursor and combined with a pyrolysis selenization strategy to prepare a copper-based sulfur / selenide composite material with abundant copper vacancies. The composite material can be used as a negative electrode material for sodium ion batteries. By one-step selenization, copper vacancies can be induced in the copper vacancies. 1.96 S and Cu 1.96 The formation of S / CuSe heterojunction, vacancy-rich Cu 1.96 S has higher conductivity and high chemical activity, and the homologous heterojunction Cu 1.96 The built-in electric field constructed at the S / CuSe interface can improve the surface reaction kinetics of the electrode material, accelerate the electron transfer rate, and thus improve the sodium storage performance of the material.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] (1) The preparation method proposed in the present invention utilizes the advantages of the novel metal organic framework compound precursor and fully utilizes the advantages of the ligands in the precursor being rich in heteroatoms such as S / N. The target product is obtained by only two steps: precursor preparation and pyrolysis and selenization. The obtained material has a stable structure, high yield, strong repeatability, and excellent performance, providing an option for exploring large-scale synthesis of sodium ion battery negative electrode materials with high rate characteristics and long cycle life;

[0017] (2) The present invention only utilizes the rapid chelation between metal ions and organic ligands, with low raw material cost and low toxicity. It adopts a simple mild co-precipitation and vapor phase selenization method, with a short process flow, simple and easy to implement, low equipment requirements, short production cycle, and great application potential;

[0018] (3) The selenium-induced defect copper-based sulfur / selenide composite material obtained by the preparation method of the present invention not only improves the conductivity of the material, accelerates the migration speed of sodium ions and shortens the electron diffusion distance, but also creates more active sites for the adsorption of sodium ions, thereby effectively improving the sodium storage capacity and rate performance of the material;

[0019] (4) When the selenium-induced defect copper-based sulfur / selenide composite material obtained by the preparation method of the present invention is used as a negative electrode material for sodium ion batteries, it is tested at a current density of 1A / g, and the initial discharge capacity can reach 528.43mAh / g. After 1000 cycles, the discharge capacity is still as high as 513.42mAh / g, showing excellent cycle performance; even after 1000 cycles at a current density of 5A / g, the discharge capacity can still be maintained at 207.7mAh / g; in the rate performance test at different current densities, the material still shows a good capacity retention rate. The above test results show that this selenium-induced defect copper-based sulfur / selenide composite material is not only endowed with high sodium storage performance, but also has excellent rate characteristics, and is a potential application material for high energy density and high power density sodium ion batteries;

[0020] (5) The present invention combines rapid co-precipitation and pyrolysis selenization strategies to construct vacancy-rich copper-based sulfides and copper-based sulfide / selenide heterojunction composite materials with multiple active sites, which significantly improves the material structure and performance, and enhances the electrochemical performance of this type of negative electrode material, including material conductivity, structural stability, sodium storage capacity, cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are SEM images of the Cys-Cu-30min precursor prepared in Example 1 and the Cys-Cu-24h precursor prepared in Example 2, wherein Figures (a), (b), and (c) are of the Cys-Cu-30min precursor, and Figures (d), (e), and (f) are of the Cys-Cu-24h precursor;

[0022] Figure 2 The Cu prepared in Example 1 1.96 S / CuSe-30min composite material and Cu prepared in Example 2 1.96 SEM images of S / CuSe-24h composite materials, where (a), (b), and (c) are Cu 1.96 S / CuSe-30min, Figures (d), (e), and (f) are Cu 1.96 S / CuSe-24h;

[0023] Figure 3 is an SEM image of the Cu2S-30min-thermal composite material prepared in Comparative Example 1;

[0024] Figure 4 is the BET diagram of the Cys-Cu-30min precursor prepared in Example 1;

[0025] Figure 51 is the XRD pattern of the Cys-Cu-30min precursor prepared in Example 1 and the Cys-Cu-24h precursor prepared in Example 2;

[0026] Figure 6 The Cu prepared in Example 1 1.96 S / CuSe-30min, Cu prepared in Example 2 1.96 XRD patterns of the Cu2S-30min-thermal composites prepared in S / CuSe-24h and Comparative Example 1;

[0027] Figure 7 The Cu prepared in Example 1 1.96 S / CuSe-30min, Cu prepared in Example 2 1.96 EIS graphs of sodium ion batteries with S / CuSe-24h and Cu2S-30min-thermal composite materials prepared in Comparative Example 1 as negative electrodes before and after 5 cycles at a current density of 1 A / g, where Figure (a) is before the cycle and Figure (b) is after 5 cycles;

[0028] Figure 8 The Cu prepared in Example 1 1.96 S / CuSe-30min, Cu prepared in Example 2 1.96 Cycling performance curves of sodium ion batteries with S / CuSe-24h, Cu2S-30min-hot prepared in Comparative Example 1, and Cu2S-24h-hot composite materials prepared in Comparative Example 2 as negative electrodes at a current density of 1A / g;

[0029] Figure 9 The Cu prepared in Example 1 1.96 Cycling performance curve of sodium ion battery with S / CuSe-30min material as negative electrode at current density of 5A / g;

[0030] Figure 10 The Cu prepared in Example 1 1.96 S / CuSe-30min, Cu prepared in Example 2 1.96 Rate performance curves of sodium ion batteries with negative electrodes of S / CuSe-24h, Cu2S-30min-hot prepared in Comparative Example 1, and Cu2S-24h-hot composite materials prepared in Comparative Example 2;

[0031] Figure 11 The Cu prepared in Example 1 1.96 Cycling performance curve of the full battery assembled with S / CuSe-30min anode and sodium nickel iron manganese oxide cathode at a current density of 0.5 A / g. DETAILED DESCRIPTION

[0032] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific examples and drawings. The following examples are implemented based on the technology of the present invention and provide detailed implementation methods and operating steps, but the scope of protection of the present invention is not limited to the following examples.

[0033] Example 1:

[0034] (1) 1.44 g of Cu(CH3COO)2•H2O was dissolved in 160 mL of deionized water to prepare solution A; 1.4544 g of cysteine ​​was then added to 640 mL of deionized water. After it was completely dissolved, 10 mL of a pre-prepared 2 mol / L NaOH solution was added. After mixing evenly, the pH of the solution was adjusted to 10.58 to obtain solution B. Solution A was then added to solution B and placed in a constant temperature 30°C water bath with magnetic stirring for 30 minutes. After the reaction was completed, the obtained mixed solution was centrifuged at 8000 rpm for 5 minutes to separate the solid product from the solution. The supernatant was discarded to obtain the lower precipitate, which was washed by centrifugation several times with deionized water and then vacuum dried at 60°C for 12 hours to obtain the Cys-Cu-30min precursor.

[0035] (2) 100 mg of Cys-Cu-30min precursor was placed in porcelain boat A, and 500 mg of selenium powder was placed in porcelain boat B. Porcelain boat B was then placed in the upstream of a dual-temperature zone tubular furnace, and porcelain boat A was placed in the downstream of a dual-temperature zone tubular furnace. The mixture was heated to 450 °C at a heating rate of 2 °C / min under a nitrogen atmosphere and kept constant at this temperature for 3 hours. After the constant temperature was reached, the mixture was naturally cooled to room temperature to obtain a selenium-induced defect copper-based sulfur / selenide material, which was recorded as Cu 1.96 S / CuSe-30min.

[0036] Example 2:

[0037] (1) 1.44 g of Cu(CH3COO)2•H2O was dissolved in 160 mL of deionized water to prepare solution A. 1.4544 g of cysteine ​​was then added to 640 mL of deionized water. After it was completely dissolved, 10 mL of a pre-prepared 2 mol / L NaOH solution was added. After mixing evenly, the pH of the solution was adjusted to 10.58 to obtain solution B. Solution A was then added to solution B and placed in a constant temperature 30°C water bath with magnetic stirring for 24 hours. After the reaction was completed, the obtained mixed solution was centrifuged at 8000 rpm for 5 minutes to separate the solid product from the solution. The supernatant was discarded to obtain the lower precipitate. The precipitate was centrifuged and washed several times with deionized water, and then vacuum dried at 60°C for 12 hours to obtain the Cys-Cu-24h precursor.

[0038] (2) 100 mg of Cys-Cu-24h precursor was placed in porcelain boat A, and 500 mg of selenium powder was placed in porcelain boat B. Porcelain boat B was then placed in the upstream of a dual-temperature zone tubular furnace and porcelain boat A was placed in the downstream of the dual-temperature zone tubular furnace. The mixture was heated to 450 °C at a heating rate of 2 °C / min under a nitrogen atmosphere and kept at a constant temperature for 3 hours. After the constant temperature was completed, the mixture was naturally cooled to room temperature to obtain a selenium-induced defect copper-based sulfur / selenide material, which was recorded as Cu 1.96 S / CuSe-24h.

[0039] Example 3:

[0040] (1) 0.64 g of Cu(CH3COO)2•H2O was dissolved in 160 mL of deionized water to prepare solution A. Subsequently, 0.7744 g of cysteine ​​was added to 640 mL of deionized water. After it was completely dissolved, 5 mL of a pre-prepared 4 mol / L NaOH solution was added. After mixing evenly, the pH of the solution was adjusted to 12 to obtain solution B. Solution A was then added to solution B and placed in a constant temperature 20°C water bath with magnetic stirring for 12 minutes. After the reaction was completed, the obtained mixed solution was centrifuged at 5000 rpm for 3 minutes to separate the solid product from the solution. The supernatant was discarded to obtain the lower precipitate. The precipitate was centrifuged and washed several times with deionized water, and then vacuum dried at 50°C for 12 hours to obtain the Cys-Cu-12min precursor.

[0041] (2) 300 mg of Cys-Cu-12min precursor was placed in porcelain boat A, and 300 mg of selenium powder was placed in porcelain boat B. Porcelain boat B was then placed in the upstream of a dual-temperature zone tubular furnace, and porcelain boat A was placed in the downstream of a dual-temperature zone tubular furnace. The mixture was heated to 300 °C at a heating rate of 3 °C / min under a nitrogen atmosphere and kept at this temperature for 1 hour. After the constant temperature was reached, the mixture was naturally cooled to room temperature to obtain selenium-induced defective copper-based sulfur / selenide material, which was recorded as Cu 1.96 S / CuSe-12min.

[0042] Example 4:

[0043] (1) 1.92 g of Cu(CH3COO)2•H2O was dissolved in 160 mL of deionized water to prepare solution A. Subsequently, 1.5488 g of cysteine ​​was added to 640 mL of deionized water. After it was completely dissolved, 15 mL of a pre-prepared 1 mol / L NaOH solution was added. After mixing evenly, the pH of the solution was adjusted to 8 to obtain solution B. Solution A was then added to solution B and placed in a constant temperature 40°C water bath with magnetic stirring for 30 hours. After the reaction was completed, the obtained mixed solution was centrifuged at 10,000 rpm for 8 minutes to separate the solid product from the solution. The supernatant was discarded to obtain the lower precipitate, which was washed by centrifugation several times with deionized water and then dried in vacuo at 80°C for 12 hours to obtain the Cys-Cu-30h precursor.

[0044] (2) 85.7 mg of Cys-Cu-30h precursor was placed in porcelain boat A, and 514.3 mg of selenium powder was placed in porcelain boat B. Porcelain boat B was then placed in the upstream of a dual-temperature zone tubular furnace, and porcelain boat A was placed in the downstream of a dual-temperature zone tubular furnace. The mixture was heated to 600 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and kept at this temperature for 5 hours. After the constant temperature was reached, the mixture was naturally cooled to room temperature to obtain a selenium-induced defect copper-based sulfur / selenide material, which was recorded as Cu 1.96 S / CuSe-30h.

[0045] Comparative Example 1:

[0046] This comparative example provides a method for preparing a copper-based sulfide composite material that has not been selenized, comprising the following steps:

[0047] (1) 1.44 g of Cu(CH3COO)2•H2O was dissolved in 160 mL of deionized water to prepare solution A. Then, 1.4544 g of cysteine ​​was added to 640 mL of deionized water. After it was completely dissolved, 10 mL of a pre-prepared 2 mol / L NaOH solution was added. The pH of the solution was adjusted to 10.58. After mixing evenly, it was solution B. Solution A was then added to solution B and placed in a constant temperature 30°C water bath with magnetic stirring for 30 minutes. After the reaction was completed, the obtained mixed solution was centrifuged at 8000 rpm for 5 minutes to separate the solid product from the solution. The supernatant was discarded to obtain the lower precipitate. The precipitate was centrifuged and washed several times with deionized water, and then vacuum dried at 60°C for 12 hours to obtain the Cys-Cu-30min precursor.

[0048] (2) 100 mg of Cys-Cu-30min precursor was placed in a porcelain boat, which was then placed in a single-temperature zone tubular furnace. The boat was heated to 450°C at a heating rate of 2°C / min under a nitrogen atmosphere and kept at this temperature for 3 hours. After the temperature was kept constant, the boat was naturally cooled to room temperature to obtain a copper-based sulfide composite material that had not been selenized, which was recorded as Cu2S-30min-hot.

[0049] Comparative Example 2:

[0050] This comparative example provides a method for preparing a copper-based sulfide composite material that has not been selenized, comprising the following steps:

[0051] (1) 1.44 g of Cu(CH3COO)2•H2O was dissolved in 160 mL of deionized water to prepare solution A. Subsequently, 1.4544 g of cysteine ​​was added to 640 mL of deionized water. After it was completely dissolved, 10 mL of a pre-prepared 2 mol / L NaOH solution was added. The pH of the solution was adjusted to 10.58. After mixing evenly, the solution was obtained as solution B. Solution A was then added to solution B and placed in a constant temperature 30°C water bath with magnetic stirring for 24 hours. After the reaction was completed, the obtained mixed solution was centrifuged at 8000 rpm for 5 minutes to separate the solid product from the solution. The supernatant was discarded to obtain the lower precipitate. The precipitate was centrifuged and washed several times with deionized water, and then vacuum dried at 60°C for 12 hours to obtain the Cys-Cu-24h precursor.

[0052] (2) 100 mg of Cys-Cu-24h precursor was placed in a porcelain boat, which was then placed in a single-temperature zone tubular furnace. It was heated to 450°C at a heating rate of 2°C / min under a nitrogen atmosphere and kept constant for 3 hours. After the constant temperature was reached, it was naturally cooled to room temperature to obtain a copper-based sulfide composite material that had not been selenized, which was recorded as Cu2S-24h-hot.

[0053] SEM testing was performed using a ZEISS Gemini SEM 300 scanning electron microscope (SEM) from Carl Zeiss, Germany. A small amount of powdered sample was coated on a black conductive adhesive and then gold-sprayed. SEM was used to characterize the sample's surface morphology and particle size.

[0054] See also Figure 1 、 Figure 2 、 Figure 3 , the above SEM pictures show that:

[0055] (1) Figure 1In Figures (a), (b), and (c), the precursor Cys-Cu-30min prepared in Example 1 exhibits an "ordered interlaced" nanobelt morphology. Each constituent unit has a diameter of approximately 6-8 μm and is evenly distributed. The thickness of a single nanobelt is approximately 5-10 nm. The constituent unit can be referred to in Figure (c), which refers to a unit composed of independent interlaced nanobelts.

[0056] (2) Figure 1 In Figures (d), (e), and (f), the Cys-Cu-24h prepared in Example 2 has a longer stirring reaction time than that in Example 1, and several nanobelt units are combined and superimposed to form a regular cluster morphology;

[0057] (3) Figure 2 In Figures (a), (b), and (c), after pyrolysis and selenization, the Cu prepared in Example 1 1.96 The S / CuSe-30min composite material still maintains the morphology of the precursor, indicating that further selenization does not change the morphology of the precursor and that the precursor has excellent structural stability. This evenly distributed "ordered staggered" nanoribbons avoids disordered stacking between individual nanoribbons, spatially exposing more sodium storage active sites and improving material utilization.

[0058] (4) Similarly, Figure 2 In Figures (d), (e), and (f), after pyrolysis and selenization, the Cu prepared in Example 2 1.96 The nanoribbon structure of the S / CuSe-24h composite material shrinks slightly, but still maintains the precursor cluster morphology;

[0059] (5) Figure 3 The morphology of the precursor can also be observed in the Cu2S-30min-heat prepared in Comparative Example 1.

[0060] The BET test was performed using the ASAP 2460 surface and porosity analyzer produced by Micromeritics Instruments, Inc., USA, to analyze the specific surface area of ​​porous materials. Figure 4 BET analysis shows that the specific surface area of ​​the Cys-Cu-30min precursor prepared in Example 1 is 115.53 m 2 / g, and the pore size is mainly concentrated in 15nm. It can be seen that the prepared new metal organic framework compound precursor has a large specific surface area and there are a large number of pores in the material. The large specific surface area of ​​the material can not only increase the wettability between the material and the electrolyte, but also help to expose more sodium storage active sites and enhance the sodium storage capacity of the electrode material. The abundant pores ensure the transmission speed of ions and electrons during the sodium storage process. The fast ion and electron transmission rate can significantly improve the rate performance of the material.

[0061] XRD tests were performed using a D / max-γβ X-ray diffractometer produced by Rigaku Corporation of Japan to analyze the composition and structure of the samples.

[0062] See also Figure 5 、 Figure 6 , the XRD pattern shows that:

[0063] (1) Figure 5 The Cys-Cu-30min precursor and Cys-Cu-24h precursor prepared in Examples 1 and 2, respectively, exhibit similar diffraction peaks and peak positions, and differ from reported possible forms of copper-based oxides, copper-based hydroxides, and copper-based sulfides, further confirming the novelty of the prepared precursor structures. Furthermore, the similar XRD diffraction peaks of the precursors prepared in Examples 1 and 2 also indicate that increasing the reaction time alters the material morphology but does not change the crystal structure and composition.

[0064] (2) Figure 6 The three composite materials prepared in Example 1, Example 2 and Comparative Example 1 have different components. In Comparative Example 1, the product obtained by direct pyrolysis of the Cys-Cu-30min precursor is Cu2S, indicating that the product is only copper sulfide in the absence of a selenium source. In Examples 1 and 2, when the Cys-Cu-30min precursor is treated with selenium powder at 450°C, the product is Cu 1.96 S and CuSe, indicating that the introduction of Se can not only form Cu containing copper vacancies 1.96 S, and can also produce CuSe species. 1.96 Compared with Cu2S, S species have abundant copper vacancies. The generation of vacancies can regulate the electronic structure of the substrate material, enhance the conductivity of the material and improve its electrochemical activity. The weak Cu-Se bond in the formed CuSe species is more conducive to the conversion reaction than that of sulfide, accelerating the diffusion of sodium ions. In addition, the formed Cu 1.96 S and CuSe can spontaneously form a homologous heterojunction. The existence of the heterojunction redistributes the charge at the interface, constructs a built-in electric field, and thus increases the internal conductivity of the material, which is conducive to the rapid transfer of electrons. In addition, although the Cu prepared in Example 1 1.96 S / CuSe-30min and Cu prepared in Example 2 1.96 S / CuSe-24h has the same Cu 1.96 S and CuSe components, but Cu 1.96 The XRD curve of S / CuSe-30min shows that Cu 1.96 The peak intensity of S is higher than that of CuSe species, while Cu 1.96The CuSe peak intensity of S / CuSe-24h is higher, indicating that the product CuSe formed by the precursor with a relatively short stirring reaction time is 1.96 S has better crystallinity, while the product CuSe formed from the precursor obtained with long stirring reaction time has better crystallinity and more exposed crystal faces.

[0065] The composite material Cu prepared in Example 1 1.96 S / CuSe-30min, the composite material Cu prepared in Example 2 1.96 S / CuSe-24h, the composite material Cu2S-30min-hot prepared in Comparative Example 1, and the composite material Cu2S-24h-hot prepared in Comparative Example 2 were all ground into powders and used as negative electrode active materials, respectively. The battery performance of the sodium ion battery negative electrode was measured using CR2032 coin-type battery test materials.

[0066] First, the Cu prepared in Example 1 1.96 The working electrode was prepared by mixing S / CuSe-30min powder, polymer binder (carboxymethyl cellulose aqueous solution, mass fraction of 1.5%) and conductive material (Super-P) to obtain a slurry, which was then coated on copper foil and dried at 80 °C for 12 h. 1.96 The mass fractions of S / CuSe-30min powder, polymer binder, and conductive material were 80 wt%, 10 wt%, and 1.5 wt%, respectively. The battery was assembled in a glove box using a Whatman glass fiber separator and a sodium metal sheet counter electrode. The electrolyte was diglyme (DIGLYME) containing NaPF6 at a 1 M concentration. The battery was tested on a LANHE (CT2001A, Wuhan, China) battery test system with a voltage window of 0.01–3 V (vs. Na). + / Na) for constant current charge / discharge and rate test of the battery. Shanghai Chenhua electrochemical workstation CHI660E was used for battery electrochemical impedance test. The test voltage was open circuit voltage and the frequency was 0.01-10 5 Hz.

[0067] The Cu prepared in Example 1 1.96 S / CuSe-30min powder was replaced by Cu prepared in Example 2 1.96 S / CuSe-24h powder, Cu2S-30min-hot powder prepared in Comparative Example 1, and Cu2S-24h-hot powder prepared in Comparative Example 2, and other methods for preparing working electrodes and testing processes are the same as those described above.

[0068] Figure 7 The composite material Cu prepared in Example 1 1.96S / CuSe-30min, the composite material Cu prepared in Example 2 1.96 The impedance diagrams of Cu2S-30min-hot composite materials prepared in Example 1 before and after 5 cycles at a current density of 1A / g when S / CuSe-24h and Comparative Example 1 were used as negative electrodes of sodium ion batteries. It can be seen from the figure that Cu2S-30min-hot has a smaller impedance before the cycle, while Cu 1.96 S / CuSe-30min and Cu 1.96 The impedance value of S / CuSe-24h is relatively large, but after 5 cycles, Cu 1.96 The impedance value of S / CuSe-30min is similar to that of Cu 1.96 The decrease in impedance is mainly due to the activation of the material. At the same time, the special nanobelt structure provides a transmission channel for electron transmission. 1.96 The formation of S components and heterostructures also helps to improve the conductivity of the material.

[0069] Figure 8 It shows that the Cu prepared in Example 1 1.96 When the S / CuSe-30min composite material is used as a negative electrode material for sodium ion batteries and tested at a current density of 1A / g, the initial discharge capacity can reach 528.43mAh / g, and the discharge capacity is still as high as 513.42mAh / g after 1000 cycles, showing excellent long-cycle performance. 1.96 The first discharge capacity of S / CuSe-24h was 654.69 mAh / g, and the discharge capacity after 1000 cycles was 435.49 mAh / g. The Cu2S-30min-hot prepared in Comparative Example 1 had a discharge capacity of 231.83 mAh / g after 499 cycles at a current density of 1 A / g, and the Cu2S-24h-hot prepared in Comparative Example 2 had a discharge capacity of 75.3 mAh / g after 384 cycles at a current density of 1 A / g, indicating that the long-term cycle performance of the composite materials prepared in Examples 1 and 2 is significantly better than that of Comparative Examples 1 and 2.

[0070] Figure 9 It shows that even after 1000 cycles at a high current density of 5A / g, the Cu prepared in Example 1 1.96 S / CuSe-30min still has a discharge capacity of 207.7mAh / g. 1.96 The excellent long-cycle stability and high capacity of the S / CuSe-30min composite material are derived from the copper vacancies in the material, which can enhance the electrochemical activity of copper-based sulfides, and the built-in electric field constructed by the heterostructure can reduce the diffusion of sodium ions.

[0071] Figure 10It shows that the composite material Cu prepared in Example 1 1.96 The capacities of S / CuSe-30min as the negative electrode material for sodium ion batteries at different current densities of 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g, and 5A / g were 542mAh / g, 560.2mAh / g, 551.4mAh / g, 539mAh / g, 524.5mAh / g, and 492.1mAh / g, respectively, indicating that the material has a good capacity retention rate. 1.96 S / CuSe-24h and Cu 1.96 S / CuSe-30min has similar rate performance and is better than Comparative Example 1 and Comparative Example 2.

[0072] Figure 11 It shows that the composite material Cu prepared in Example 1 1.96 When S / CuSe-30min was used as the negative electrode and assembled into a full battery with a sodium nickel iron manganese oxide positive electrode, the capacity was maintained at 196.61 mAh / g after 100 cycles at a current density of 0.5 A / g. These results demonstrate that this composite material, rich in copper vacancies and possessing a homogeneous heterojunction structure, exhibits improved long-cycle performance and high-rate characteristics, making it a potential material for high-energy-density and high-power-density sodium-ion batteries.

[0073] The above description is merely an embodiment of the present invention and does not constitute any form of limitation to the present invention. The present invention may also have other forms of embodiments based on the above structures and functions, which are not listed here one by one. Therefore, any simple modification, equivalent changes, and modifications made to the above embodiments by any person skilled in the art in accordance with the technical essence of the present invention without departing from the scope of the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a selenium-induced defect copper-based sulfur / selenide material, characterized in that: The specific steps include: (1) Dissolve copper acetate in water to prepare solution A, wherein the molar concentration of copper acetate in solution A is 0.02-0.06 mol / L; dissolve cysteine ​​in water, and after cysteine ​​is completely dissolved, add NaOH solution to adjust the pH value of the above solution to alkaline to obtain solution B, wherein the molar concentration of cysteine ​​in solution B is 0.01-0.02 mol / L; then add solution A to solution B, and stir the reaction in a constant temperature water bath, wherein the temperature of the constant temperature water bath is 20-40°C. After the reaction is completed, centrifuge the obtained mixed solution, discard the upper layer of liquid, obtain a lower layer of precipitate, and wash the precipitate with water for multiple times by centrifugation, and then vacuum dry to obtain a Cys-Cu precursor; (2) Place the Cys-Cu precursor in porcelain boat A and the selenium powder in porcelain boat B. The mass ratio of the Cys-Cu precursor to the selenium powder is 1:1~1:

6. Then place porcelain boats A and B in the downstream and upstream of a double-temperature zone tubular furnace, respectively. Heat the temperature to 300~600℃ at a heating rate of 2~5℃ / min under an inert atmosphere and keep the temperature constant for 1~5 hours. After the constant temperature ends, naturally cool to room temperature to obtain selenium-induced defective copper-based sulfur / selenide materials.

2. The method for preparing the selenium-induced defective copper-based sulfur / selenide material according to claim 1, characterized in that: In step (1), the water used is deionized water; the concentration of the NaOH solution is 1-4 mol / L, the volume of the added NaOH solution is 5-15 mL, and the pH value of solution B is 8-12.

3. The method for preparing the selenium-induced defective copper-based sulfur / selenide material according to claim 1, characterized in that: In step (1), the stirring reaction time is 0.2 to 30 hours.

4. The method for preparing the selenium-induced defective copper-based sulfur / selenide material according to claim 1, characterized in that: In step (1), the rotation speed of centrifugal separation is 5000-10000 rpm, the time of each centrifugal separation is 3-8 minutes; and the drying temperature is 50-80°C.

5. The method for preparing the selenium-induced defective copper-based sulfur / selenide material according to claim 1, characterized in that: In step (2), the inert atmosphere is N2 atmosphere.

6. The selenium-induced defective copper-based sulfur / selenide material obtained by the preparation method according to any one of claims 1 to 5.

7. The selenium-induced defective copper-based sulfur / selenide material according to claim 6, characterized in that: The material contains Cu 1.96 S and CuSe, and Cu 1.96 A homologous heterojunction is formed between S and CuSe.

8. Use of the selenium-induced defect copper-based sulfur / selenide material as claimed in claim 6 as a negative electrode material for sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of high-volumetric-specific-capacity sodium storage material based on sulfur-doped iron selenide

    CN116332136A

  • Sodium-ion battery defect-rich copper sulfide / carbon composite negative electrode material and preparation method thereof

    CN116741943A